2007
DOI: 10.1590/s0365-05962007000400006
|View full text |Cite
|
Sign up to set email alerts
|

Histiocitose de células de Langerhans: relato de caso e revisão da literatura

Abstract: Os autores descrevem caso de paciente de dois anos de idade, apresentando lesões pápulovesiculosas no tronco que evoluíram para crostas, além de tumorações com necrose na região cervical. Durante a internação, observou-se estrabismo convergente à direita, de instalação súbita. Os exames histopatológico e imuno-histoquímico das lesões cutâneas comprovaram tratar-se de histiocitose de células de Langerhans, sendo o paciente submetido à quimioterapia com melhora importante do quadro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
9

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 6 publications
0
11
0
9
Order By: Relevance
“…7 Extensive cutaneous lesions can be treated with low dose systemic corticotherapy and chemotherapy (usually a sole drug, most commonly vinblastine, methotrexate and etoposide). 1,7,9 More recently some studies have shown a good response to thalidomide. 6,11 The drug has antinflammatory and antineoplastic effects and works through inhibition of TNF and IL-6, which have increased expression in LCH.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…7 Extensive cutaneous lesions can be treated with low dose systemic corticotherapy and chemotherapy (usually a sole drug, most commonly vinblastine, methotrexate and etoposide). 1,7,9 More recently some studies have shown a good response to thalidomide. 6,11 The drug has antinflammatory and antineoplastic effects and works through inhibition of TNF and IL-6, which have increased expression in LCH.…”
Section: Discussionmentioning
confidence: 99%
“…1 The ethiology is unknown and some believe it is probably a secondary condition to viral infections or immunologic imbalance; neoplasic and genetic origins have also been proposed. 1,4,6,7,9 It can develop at any age but the incidence peak is between 1 and 3 years of age. 2 Patients with focal lesions are usually older than those with multisystem disease.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations